品質評価方法 (2022)
【課題】より精度の高い遺伝子検査の品質管理手法を提供する。【解決手段】検査に用いられる前記遺伝子パネル検査の種別に応じて前記標準遺伝子の組み合わせが異なる品質管理試料を調製し、検体から配列解析用試料を調製し、前記品質管理試料に含まれる前記標準遺伝子および前記配列解析用試料に含まれる遺伝子の配列情報をシーケンサーにより取得し、前記配列情報に基づいて、前記遺伝子パネル検査の品質評価に用いられる指標をコンピュータによって出力する、標準遺伝子を用いて遺伝子パネル検査の品質を評価する。【選択図】図２ Disclosed is a quality evaluation method performed in a genetic test for testing a gene in a sample collected from a subject, for a plurality of types of gene mutations that include a first type gene mutation and a second type gene mutation different from the first type gene mutation, and the quality evaluation method includes: preparing a quality control sample that includes a first reference gene having the first type gene mutation, and a second reference gene having the second type gene mutation; obtaining sequence information of the genes included in the quality control sample; and outputting an index for evaluation of a quality of the genetic test, based on the sequence information having been obtained.